Temporal and Spatial Philosophy in Confessions of Tam Seti: Tin Amoud and Ain El Zana by Ezzedine Mihoubi - Wushishi, Ibrahim Adam; Sehui, Idris (Dzil Majaz: Journal of Arabic Literature, 2023)
The study attempts to reveal the aesthetic system and techniques of fictional work, the hidden secrets of narrative narrative expression, and its highly distinguished means in Tam City novel by Azzedine Mihoubi. In order to achieve three things, the first: the work of the contemporary Algerian-Arab novelist and its artistic development, the second: time and the philosophy of the narrator in defining it, and the third: time and place and the bankruptcy of the narrator in his allocation. Because the language used in the novel gave it a rare and beautiful soul, which distinguishes it from most Algerian novels.